2016
DOI: 10.2807/1560-7917.es.2016.21.10.30159
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of infectious Zika virus from saliva and prolonged viral RNA shedding in a traveller returning from the Dominican Republic to Italy, January 2016

Abstract: We report the isolation of infectious Zika virus (ZIKV) in cell culture from the saliva of a patient who developed a febrile illness after returning from the Dominican Republic to Italy, in January 2016. The patient had prolonged shedding of viral RNA in saliva and urine, at higher load than in blood, for up to 29 days after symptom onset. Sequencing of ZIKV genome showed relatedness with strains from Latin America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
163
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(181 citation statements)
references
References 33 publications
5
163
0
13
Order By: Relevance
“…The higher number of samples and the fact that real samples were used instead of spiked ones may be the reason why we observed different rates, mainly in urine samples which had a low positive rate in this study. Barzon et al 2016 observed prolonged shedding of ZIKV in saliva and urine up to 29 days in one patient by qPCR and showed that during the first days of infection, the viral load is constantly changing, and at certain time points saliva showed higher ZIKV RNA (copies/mL) compared with urine [5]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The higher number of samples and the fact that real samples were used instead of spiked ones may be the reason why we observed different rates, mainly in urine samples which had a low positive rate in this study. Barzon et al 2016 observed prolonged shedding of ZIKV in saliva and urine up to 29 days in one patient by qPCR and showed that during the first days of infection, the viral load is constantly changing, and at certain time points saliva showed higher ZIKV RNA (copies/mL) compared with urine [5]. …”
Section: Discussionmentioning
confidence: 99%
“…It is transmitted among humans usually by Aedes mosquito species, but dissemination by sexual transmission [2], perinatal [3] and blood transfusion [4] have also been reported. Symptoms appear in 20% of infected individuals and include fever, cutaneous rash, headache, conjunctivitis, myalgia and arthralgia [5]. After the USA’s ZIKV outbreak in 2016, a sudden increase in microcephaly and Guillain-Barré syndrome (GBS) related with ZIKV infection prompted the World Health Organization (WHO) to declare a public health emergency of international concern [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike DENV, ZIKV is detected in the urine 6 , saliva 5 and semen 4 (which allows potential transmission by sexual contact 25 ), suggesting that the virus is stable enough to withstand harsh conditions. This is consistent with our infection assay showing that ZIKV is more thermally stable than DENV.…”
mentioning
confidence: 99%